Analisis Efektivitas Media Book Creator pada Mata Pelajaran Pendidikan Pancasila di Kelas V Sekolah Dasar (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effectiveness of Book Creator-based digital learning media to improve students' Pancasila Education learning outcomes. This research is included in the type of development research (Research and Development) using the ADDIE development model. After the media is applied in the learning process, an effectiveness test is carried out to assess the extent of the effectiveness of the media, by comparing the results of the pretest and posttest of the students. Therefore, the data collection technique used is a test. The effectiveness test was analyzed using the percentage formula. This effectiveness test was carried out in three schools, namely SDN 22 Tanjung which showed an average pretest score percentage of 73.33%, while the posttest reached 88.67%. At SDN 3 Tanjung, the percentage of pretest scores is 78%, and it increases to 90% in the posttest. Meanwhile, at SDN 15 Tanjung, the average pretest score was 76.25% and increased to 91.87% in the posttest. Based on the analysis of the N-Gain test in the three schools, an average score of 0.603307 was obtained which was included in the medium category. Thus, it can be concluded that the use of Book Creator media is effective in supporting the learning process.